MORPHOLOGY AND TENSILE PROPERTIES OF PVA/SNAIL MUCIN NANOFIBER MEMBRANES - Aris Widyo Nugroho; Imam Nur Sholeh; Harini Sosiati (Jurnal Sains Materi Indonesia, 2018)
MORPHOLOGY AND TENSILE PROPERTIES OF PVA/SNAIL MUCIN NANOFIBER MEMBRANES. Snail mucin has been widely known to contain agents with wound healing properties. A preliminary research with regard to the potential to manufacture composite nanofibrous membranes of polyvinyl alcohol (PVA) and snailmucin (SM) by the electrospinning technique forwound dressing applications has been conducted. The effect of SM concentration on the morphology and tensile properties of PVA/SM nanomembrane has been investigated. The PVA/SMsolutions with various concentration of SM(0%, 2%, 4%, dan 6%)(w/v) were electrospun at the optimized process parameters. The morphology nanofiber membranes was observed by scanning electronmicroscopy and the average diameters of prepared nanofibers was determined by image analysis technique. The tensile test was conducted to examine the tensile properties of the nanofiber membranes being prepared according to ASTM D882. The PVA/SM nanofibre membrane possessing the tensile strength and tensile strain ranging between 3.48-5.37 MPa and 101.25- 157.13 %, respectively were successfully fabricated. Themembrane of 10%(w/v) PVA/ 2%(w/v) SMachieved the highest values of tensile strength. This phenomenon has been associated to the uniformity of fiber size diameter distribution within the membranes. It was expected that further optimization of the processing would allow development of the tensile properties compatibility requirement with this being the subject of future work by the authors.